A new model to improve service quality in the property management industry - Chiang, Ting-Yi; Perng, Yeng-Horng (International Journal of Strategic Property Management, 2018)
The categories and quality attributes of property services valued by customers in Taiwan are discussed in this paper. We proposed a hybrid model that combines SERVQUAL, the Kano model, and the Refined Kano model in order to examine a sample of three hundred customers. The results show that the new model analysis validated the effectiveness of the proposed approach while maintaining classification power at par with the Kano questionnaire; a lower turnover rate of service staff (X14) shall be considered the quality attribute of Potential (P), inferring that a lower dismissal rate of service staff allows the management to reduce oft-incurred training expenditures and maintain the company’s competitiveness. Indeed, a more consumer-oriented point of view and differentiated service strategies may effectively resolve the cognitive gap (and eventually the overall gap) between property service staff and customers. Consequently, property services providers would do well either to collaborate with research institutions or to carry out periodic surveys using questionnaires to improve the quality of their services.